Achievements, Prospects and challenges of research in the Faculty of Arts at the Universidad Nacional, Costa Rica - Ugalde Viquez, Aracelly (2012)
As part of this project, we conducted a quantitative and qualitative study to determine the role of research projects. The reporting period covers the projects implemented between 2007 and 2011, all of them are part of the work of the Faculty of Arts. It aims to recognize the features, themes, geographical coverage, results, conclusions and the importance of the projects in the humanities and scientific communications. Moreover, since these projects reflect our identity and thought, compares the methodology used in its operation with international quality parameters. As a result of this study, we propose a forward-looking research and its impact on the academic work of the University.